(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: DNA damage reflects a balance between oxidative stress and DNA repair ability which associates with breast cancer risk. Objective: Assessment of the oxidative DNA damage in women with breast tumors using comet tail length (CTL) and comet tail moment (CTM) to measure the extent of single strand DNA breaks in addition to 8-hydroxy deoxy guanosine (8-OHdG) levels and numbers of DNA lesions. Methods: Blood leukocytes and post operative tumor specimens were taken from 40 females with newly diagnosed breast tumors (age 24-75 years) and leukocytes of 40 healthy controls (age range 24-50 years). The cells were subjected to single cell agarose gel electrophoresis and the severity of DNA damage was quantitated by computer image analysis. The level of the 8-OHdG was measured by ELISA and numbers of DNA lesions was estimated by special formula. Results: There were highly significant differences(P